2005
DOI: 10.1177/0022167805280265
|View full text |Cite
|
Sign up to set email alerts
|

A Critique of Posttraumatic Stress Disorder and the DSM

Abstract: Posttraumatic stress disorder (PTSD) is one of the few DSM categories that was created and became widely accepted as a result of people other than psychiatrists wanting it. Even progressive practitioners tend to assume that it is essentially well constructed and benign. This article shows otherwise. The article fundamentally problematizes PTSD. It demonstrates that the category PTSD is confused, reductionist, contradictory, and arbitrary and that it pathologizes purposeful and valuable coping strategies common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 4 publications
0
46
0
Order By: Relevance
“…Previous research with survivors of sexual and gender-based violence has found that medicalising women's distress fails to adequately highlight women's own gendered and collective experiences of FGM within its cultural context and neglects survivors' resilience (Burstow, 2005;Liebling-Kalifani, 2009;. Placing greater emphasis on culturally-sensitive frameworks provides a starting point that recognises women's own capacities to deal with their experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research with survivors of sexual and gender-based violence has found that medicalising women's distress fails to adequately highlight women's own gendered and collective experiences of FGM within its cultural context and neglects survivors' resilience (Burstow, 2005;Liebling-Kalifani, 2009;. Placing greater emphasis on culturally-sensitive frameworks provides a starting point that recognises women's own capacities to deal with their experiences.…”
Section: Introductionmentioning
confidence: 99%
“…One example is the classification of OCD that includes bizarre behaviors, such as the compulsive cleaner who washes her hands 200 times per day but leaves her legs and feet unwashed for months (see Rachman & Hodgson, 1980, p. 65), together with non-mad behaviors such as PTSD which is an understandable response to extreme trauma, only because both display observable anxiety (APA, 2000). As noted by Burstow (2005), in her critique of the DSM categorization of PTSD as an anxiety disorder,…”
Section: Discussionmentioning
confidence: 99%
“…Critics have argued that the DSM is not truly atheoretical as it claims to be, as evidence suggests that its diagnostic categories are implicitly determined by the medical model (e.g., Burstow, 2005;Follette & Houts, 1996). As noted by Pilecki, Clegg, and McKay (2011), the DSM "has not provided a neutral collection of observation-based syndromes and it seems naive to have ever expected such an outcome" (p. 199).…”
Section: Shortcomings Of Dsm's False Diagnostic Approachmentioning
confidence: 99%
“…As noted by Pilecki et al since the psychoanalytic therapy refers to underlying conflicts which necessitate relatively long intervention, "There was a desire to remove neurosis from diagnostic terminology and focus instead on descriptions of severe pathology that were more rare and justifiable in terms of reimbursement " (p. 196). Second, although the DSM claimed to be neutral, in reality, medical models implicitly determined the diagnostic categories (Burstow, 2005;Follette & Houts, 1996). As claimed by Pilecki et al (2011) www.ccsenet.org/ijps…”
Section: The Need To Reinstate Neurosismentioning
confidence: 99%